QuickTime toolkit - Apple Computer, Inc. (Amsterdam ; Boston : Morgan Kaufmann, 2004)
"Buried inside QuickTime are a host of powerful tools for creating, delivering, and playing digital media. The official QuickTime documentation explains 'what' each API function does. But knowing what each function does isn't enough to allow a developer to take full advantage of QuickTime. QuickTime Toolkit fills in the gap--providing plenty of practical examples of 'how' to use QuickTime to perform all kinds of useful tasks. More importantly, [this book] goes beyond 'how' and into 'why' --providing readers with a deeper understanding of QuickTime and how to benefit from using it in their own products."--Peter Hoddie, cofounder of Kinoma and former QuickTime architect QuickTime Toolkit, Volume Two continues the step-by-step investigation of programming QuickTime, the elegant and powerful media engine used by many of Apple's industry-leading services and products (such as the iTunes music store, iMovie, and Final Cut Pro) and also used by a large number of third-party applications. This second collection of articles from the author's highly regarded column in MacTech Magazine builds upon the discussion of playback techniques and media types presented in the first volume to cover advanced types of QuickTime media data, including video effects, Flash tracks, and skins. It shows how to capture audio and video data, broadcast that data to remote computers, play movies full screen, and load movies asynchronously. QuickTime Toolkit Volume Two also shows how to integrate Carbon events into your Macintosh application and how to work with Macintosh resources in your Windows application. Part of the official QuickTime Developer Series, publishing the finest books on QuickTime in cooperation with Apple. *Includes a CD-ROM with numerous code examples in C to help you get started with your own applications *Written by one of Apple's premier media engineers skilled in revealing QuickTime's sophisticated technology to programmers *Offers many undocumented insider tips for making applications that work well in both Mac OS and Windows.
v. 1. Basic movie playback and media types.--v. 2. Advanced movie playback and media types.
Includes indexes.
Keywords: Motion pictures -- Editing -- Data processing; QuickTime; Electronic books